DIVERSITY OF SHRUBS AND TREES IN THE ISLAND TOWNS OF NORTHERN SAMAR, PHILIPPINES - Minguez-Galenzoga, Divina (International Journal of Research -GRANTHAALAYAH, 2019)
This study aimed to identify the shrubs and trees in the five island towns of Northern Samar, Philippines; determine their abundance, community structure; and economic uses to the locals. Four barangays in every island town represented the north, south, east, and west sides. Line Intercept Transect (LIT) at intervals of 100m and plot method with an area of 10m x 10m were used in gathering the data. Transect walks, field plots, and transects were also used in gathering data. There were 207 species of shrubs and trees belonging to 152 genera and 64 families. Shrubs constituted 55.33% and trees 44.67% of the total number of species. Mangifera indica (Anacardiaceae) ranked first in relative density (25.50%), relative frequency (25.30%), and importance value (59.15%). Plots in the island of Laoang were observed to have the highest Shannon Diversity Index (3.25%) and Simpson’s Dominance Index (1.86%). The most abundant shrub and tree species in the island towns were Citrus microcarpa (Cucurbitaceae) and Mangifera indica (Anacardiaceae) respectively. The least abundant shrub and tree species were Gardenia jasminoides (Rubiaceae) and Cananga odorata (Annonaceae) respectively. There were more species of shrubs and trees in the island town of Laoang than in the other four island towns.